2004
DOI: 10.1016/j.mrgentox.2004.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial mutagenicity of the three isomeric dicyclopenta-fused pyrenes: the effects of dicyclopenta topology

Abstract: Cyclopenta[cd]pyrene (1) and its congeners dicyclopenta [cd,mn]-(2), dicyclopenta [cd,fg]-(3), dicyclopenta [cd,jk]pyrene (4), which were all identified as constituents of combustion exhausts, as well as their partially hydrogenated derivatives 3,4-dihydrocyclopenta[cd]-(5), 1,2,4,5-tetrahydrodicyclopenta[cd,mn]-(6), 5,6,7,8-tetrahydrodicyclopenta[cd,fg]- (7) and 1,2,6,7-tetrahydrodicyclopenta[cd,jk]pyrene (8), were assayed for mutagenicity in the Salmonella typhimurium strain TA98 using different concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…one-step epoxidation of the five-membered ring olefinic bond. This was also observed for compounds 2-4 [21]. The results suggested that the ultimate mutagenic active forms in the presence of S9-mix are the di-epoxides 6-8 (Fig.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…one-step epoxidation of the five-membered ring olefinic bond. This was also observed for compounds 2-4 [21]. The results suggested that the ultimate mutagenic active forms in the presence of S9-mix are the di-epoxides 6-8 (Fig.…”
Section: Introductionsupporting
confidence: 62%
“…2-5 the dose-response curves are shown for the direct-acting (−S9-mix) and metabolic activation-dependent mutagenicity (+S9-mix) for the (di-)epoxides 5-8. The results are compared with those previously found for CP-PAH 1-4 in the same dose range (0.0-2.0 g/plate) and under similar conditions [21]. The specific mutagenic activity of 1-8, viz.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations